2021
DOI: 10.3390/jpm11101030
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Scores Contribute to Personalized Medicine of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disorder characterized by the loss of dopaminergic neurons. The vast majority of PD patients develop the disease sporadically and it is assumed that the cause lies in polygenic and environmental components. The overall polygenic risk is the result of a large number of common low-risk variants discovered by large genome-wide association studies (GWAS). Polygenic risk scores (PRS), generated by compiling genome-wide significant variants, are a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…This has recently been pointed out by several studies conducted in the Caucasian population from which a cohort of Slovenian patients included in the reported study originate as well. The latter confirms the reliability of this finding, which should be accounted for in future polygenic risk scores for prediction of PD since none of them so far take into account the VDR genotype ( Ibanez et al, 2017 ; Dehestani et al, 2021 ). Additionally, patients with at risk VDR genotypes are suitable candidates for close monitoring of vitamin D levels.…”
Section: Discussionsupporting
confidence: 78%
“…This has recently been pointed out by several studies conducted in the Caucasian population from which a cohort of Slovenian patients included in the reported study originate as well. The latter confirms the reliability of this finding, which should be accounted for in future polygenic risk scores for prediction of PD since none of them so far take into account the VDR genotype ( Ibanez et al, 2017 ; Dehestani et al, 2021 ). Additionally, patients with at risk VDR genotypes are suitable candidates for close monitoring of vitamin D levels.…”
Section: Discussionsupporting
confidence: 78%
“…In order to test the predictive power of the obtained genetic longevity scores, we performed ROC curve analysis (Fig 4), which showed that all four scores were satisfactory for predicting the possibility of reaching the longevity milestones (90+ and 95+ years) that were above the theoretical cut-off value for this test of 0.5 [35,36]. However, with an AUC score of 0.690, wGLS90 is a more predictive longevity score for survival to the age of 90, and uGLS90 with an AUC score of 0.662 is the less predictive.…”
Section: Plos Onementioning
confidence: 99%
“…In summary, PGS may be a useful translational research tool in this arena to test hypotheses about the nature of associations between individual differences in musicality and health conditions, 61,62 with its maximal specificity to identify subsets of patients who may benefit from particular clinical interventions customized to them (e.g., Ref. 63), but PGS is not a tool that can make specific individual determinations.…”
Section: For Common Misconceptions About Heritability)mentioning
confidence: 99%